Asynchrony among local communities stabilises ecosystem function of metacommunities. (24th October 2017) - Wilcox, Kevin R.; Tredennick, Andrew T.; Koerner, Sally E.; Grman, Emily; Hallett, Lauren M.; Avolio, Meghan L.; La Pierre, Kimberly J.; Houseman, Gregory R.; Isbell, Forest; Johnson, David Samuel; Alatalo, Juha M.; Baldwin, Andrew H.; et al.
Abstract: Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species' populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.